Uji Potensi Isolat Rhizobakteri Menekan Pertumbuhan Jamur Antraknosa Cabai Merah (Capsicum annum L.) secara In Vitro - Ifa Mahmuda; Andree Saylendra; Endang Sulistyorini; Sulastri Isminingsih (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
The main problem in red chili production is the attack of pests and diseases, particularly anthracnose caused by the fungus Colletotrichum spp., which can reduce yields by up to 60% if not controlled. Control methods typically involve the use of fungicides; however, excessive use can lead to pathogen resistance and negative environmental impacts. Therefore, there is a need for more environmentally friendly control alternatives, such as the utilization of biocontrol agents like rhizobacteria. This study aims to evaluate the inhibitory capacity and potential of rhizobacteria in suppressing the growth of Colletotrichum sp. fungi. In the first phase, 20 rhizobacterial isolates were tested, and 5 isolates were selected for further testing in the second screening phase. The research employed a non-factorial Completely Randomized Design, consisting of 6 rhizobacterial treatments with 5 replications, resulting in a total of 30 experimental units. The best inhibitory capacity was observed in rhizobacterial isolate RB 5 (2.44%) and RB 2 (2.41%). All rhizobacterial isolates exhibited variations in colony characteristics, color, and staining results. Additionally, all tested isolates showed potential for phosphate (P) solubilization, indicated by the formation of clear zones around the rhizobacterial suspensions. The highest catalase enzyme production was observed in isolates RB 3 and RB 5. While the rhizobacterial isolate RB 3 demonstrated pathogenicity, as evidenced by the softening of potato tissue after being scratched with the isolate, it still maintained a good inhibitory effect against the growth of Colletotrichum sp.